Analisis Karakteristik Arus Lalu Lintas Dengan Model Greenshield, Greenberg Dan Underwood Di Ruas Jalan KHZ Musthofa Kota Tasikmalaya - Sholahudin, Farhan (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2021)
In the planning, design and determination of various transportation system policies, the theory of traffic flow characteristics plays a very important role. To facilitate the application of the theory of traffic characteristics, a mathematical approach is used to analyze the phenomena that occur in the traffic flow. One approach to understanding traffic behavior is to describe it in mathematical and graphical relationships by paying attention to the relationship between speed (S), density (D) and volume (V) of traffic. The purpose of this study was to analyze the characteristics of traffic flow on Jalan KHZ Musthofa which is the primary arterial road connecting vital locations in the City of Tasikmalaya using several mathematical models, namely the greenshield, greenberg and underwood models. This study has an urgency to determine the characteristics of the appropriate traffic flow and closest to the existing conditions in the field so that it can be used as a basis for determining the level of service on a road segment. This is an answer and proof that there is no road segment that has the same traffic flow characteristics even though the environmental conditions are very similar. From the results of data analysis, it can be seen that the traffic characteristics that are most appropriate to the existing conditions in the field based on the analysis of the selected model on the KHZ Musthofa Road Section, namely the Greenshield Model with free flow speed (Sf) = 52,043 km/hour, congestion density that occurs (Dj ) = 70,207 pcu/km and the maximum volume or road capacity (Vmax) = 3,654,088 pcu/hour. The structure of the model of the relationship between velocity (S) and density (D) is S = 50.96 - (0.66)D, for the model of the relationship between volume (V) and density (D) is V = 50.96 D - (0.66) D2, for the model of the relationship between volume (V) and velocity (S), namely V = 77.13 S – (0.66) S2.